Good Governance Based on Bugis Local Values: Integrating Taro Ada Taro Gau Values into the Concept of Village-Owned Enterprises (BUMDes) Governance - Windy Indriyani; Wawan Andi Saputra; Mustianti Mustianti; Nurariq Ahmad; Febrina Nur Ramadhani (Phinisi Applied Accounting Journal, 2026)
Purpose: This study aims to show how the integration of local Bugis cultural values of Taro Ada Taro Gau can strengthen the concept of Good Governance in BUMDes governance, to create a village government system that is more transparent, accountable, and free from corruption .Method: This research uses the Systematic Literature Review (SLR) method with a normative and descriptive approach, to analyze the relationship between the principles of Good Governance and local Bugis ethical values .Findings: The results of this study indicate that the application of Good Governance principles alone is not sufficient to prevent corruption at the local government level, particularly in the management of Village-Owned Enterprises (BUMDes). Strengthening the ethical and moral values of village officials is necessary. The implementation of the Taro Ada Taro Gau values, which emphasize harmony between words and actions, can strengthen the integrity of village officials, increase transparency and accountability, and contribute to the prevention of corrupt practices.